Communication for Family Wellbeing : The Role Department of Population Control, Women's Empowerment, and Child Protection in Surabaya - Argieta Najwa; Dyva Claretta (Jurnal Dakwah dan Komunikasi, 2024)
Poverty is a complex problem that has a broad impact on various aspects of life, such as health, education and family welfare. This research aims to explore the role of the Surabaya Population Control, Women's Empowerment and Child Protection (DP3A) Department in overcoming poverty through development communication and group communication approaches. Using descriptive qualitative methods and in-depth interviews, this research found that DP3A has implemented three main programs: School for Great Parents (SOTH), School for the Elderly Resilient (SELANTANG), and Efforts to Increase Acceptor Family Income (UPPKA). These three programs function as a means to convey development messages to the people of Surabaya through training, outreach and mentoring. SOTH provides education about good parenting patterns to parents, SELANTANG empowers the elderly to remain active and productive, while UPPKA helps families increase their income through entrepreneurship training. The research results show that the group communication strategies implemented by DP3A, such as interactive discussions and training, are effective in conveying personal and in-depth information, thereby improving family welfare and empowering people to get out of poverty.